Pan-cancer analysis of the angiotensin II receptor-associated protein as a prognostic and immunological gene predicting immunotherapy responses in pan-cancer - Hong, Kai; Zhang, Yingjue; Yao, Lingli; Zhang, Jiabo; Sheng, Xianneng; Song, Lihua; Guo, Yu; Guo, Yangyang (Frontiers in Cell and Developmental Biology, 2022)
Background: Understanding interior molecular mechanisms of tumorigenesis and cancer progression contributes to antitumor treatments. Angiotensin II Receptor Associated Protein (AGTRAP) has been confirmed to be related with materials metabolism in metabolic disease and can drive progression of hepatocellular carcinoma and colon carcinoma. However, functions of AGTRAP in other kinds of cancers is unclear and a pan-cancer analysis of AGTRAP has not been carried out. Methods and Materials: We downloaded data from The Cancer Genome Atlas (TCGA) and Genotype-Tissue Expression dataset (GTEx) and The Human Protein Atlasdatabase (THPA) databases, then used R software (version 4.1.1) and several bioinformatic tools to conduct the analysis. Results: In our study, we evaluated the expression of AGTRAP in cancers, such as high-expression in breast cancer, lung adenocarcinoma, and glioma and low-expression in kidney chromophobe; further revealed that high-expression of AGTRAP is significantly related with poor prognosis in glioma, liver cancer, kidney chromophobe, and so on. We also explored the putative functional mechanisms of AGTRAP across pan-cancer, such as endoplasmic reticulum (ER) pathway, endocytosis pathway, and JAK-STAT signaling pathway. Besides, the connection between AGTRAP and tumor microenvironment (TME), tumor mutation burden (TMB), and immune-related genes were proved. Conclusion: Our study supplied comprehensive evidences of the roles of AGTRAP in different kinds of cancers and supported the relationship of AGTRAP and tumorous immunity.